Karakteristik Pemerataan Pendidikan Kabupaten/Kota di Provinsi Sumatera Barat dengan Aanalisis Biplot - Elza Vinora; Irwan Irwan; Yenni Kurniawati (Journal of Mathematics UNP, 2019)
Abstract – Distribution of education in Sumatera Barat has become one of the priotities in the development of human resources. But until now, education in Sumatera Barat is still not evenly distributed. This can be see from the low of Participation Rough figures in certain areas as well as uneven distribution of theachers and educational fasilities. The purpose of this research is to provide information to local authorities about the state of education in local region to produce an appropriate policy regarding development of educational infrastructure and teachers distribution. Biplot is a graphic technique that presents together information about the object of observation and variabels in one plot. In this research, the three biplots is for elementary school education, junior high schools and high schools. Based biplot display, educational equity District / City in West Sumatra for all levels of education has not been evenly distributed.